Interdisciplinary consensus statement on indication and application of a hydrogel spacer for prostate radiotherapy based on experience in more than 250 patients - Müller, Arndt-Christian; Mischinger, Johannes; Klotz, Theodor; Gagel, Bernd; Habl, Gregor; Hatiboglu, Gencay; Pinkawa, Michael (Radiology and oncology, 2016)
Abstract Background The aim of the study was to reach a consensus on indication and application of a hydrogel spacer based on multicentre experience and give new users important information to shorten the learning curve for this innovative technique. Methods The interdisciplinary meeting was attended by radiation oncologists and urologists, each with experience of 23 - 138 hydrogel injections (SpaceOAR®) in prostate cancer patients before dose-escalated radiotherapy. User experience was discussed and questions were defined to comprise practical information relevant for successful hydrogel injection and treatment. Answers to the defined key questions were generated. Hydrogel-associated side effects were collected to estimate the percentage, treatment and prognosis of potential risks. Results The main indication for hydrogel application was dose-escalated radiotherapy for histologically confirmed low or intermediate risk prostate cancer. It was not recommended in locally advanced prostate cancer. The injection or implantation was performed under transrectal ultrasound guidance via the transperineal approach after prior hydrodissection. The rate of injection-related G2-toxicity was 2% (n = 5) in a total of 258 hydrogel applications. The most frequent complication (n = 4) was rectal wall penetration, diagnosed at different intervals after hydrogel injection and treated conservatively. Conclusions A consensus was reached on the application of a hydrogel spacer. Current experience demonstrated feasibility, which could promote initiation of this method in more centres to reduce radiation-related gastrointestinal toxicity of dose-escalated IGRT. However, a very low rate of a potential serious adverse event could not be excluded. Therefore, the application should carefully be discussed with the patient and be balanced against potential benefits.